Raspberry danish murder - Fluke, Joanne, 1943- (Fluke, Joanne, 1943- Hannah Swensen mystery., 2018)
Hannah has felt as bitter as November in Minnesota since Ross vanished without a trace and left their marriage in limbo. Still, she throws herself into a baking frenzy for the sake of pumpkin pie and Thanksgiving-themed treats while endless holiday orders pour into The Cookie Jar. Hannah even introduces a raspberry Danish pastry to the menu, and P.K., her husband<U+2019>s assistant at KCOW-TV, will be one of the first to sample it. But instead of taking a bite, P.K., who is driving Ross<U+2019>s car and using his desk at work, is murdered. Was someone plotting against P.K. all along or did Ross dodge a deadly dose of sweet revenge? Hannah will have to quickly sift through a cornucopia of clues and suspects to stop a killer from bringing another murder to the table . . .